THE RENAISSANCE KING: ZAIN-UL-ABIDIN’S REIGN IN KASHMIR - Shabir Ahmad Lone; R. Abida Begum; S. Nazeemunnisa Begum; Javad Ahmad Mir; Mohammad Ishaq Lone (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Sultan Zain-ul-Abidin, popularly known as Budshah (The Great King), was a transformative ruler whose reign (1420–1470 A.D.) marked a golden era in Kashmiri history. Revered for his visionary leadership, he championed religious tolerance, cultural revival, and economic prosperity, earning him the title of "The Renaissance King." Zain-ul-Abidin fostered harmony among Kashmir’s diverse communities, creating an environment of inclusivity and social cohesion. His reign saw a flourishing of arts, crafts, and literature, making Kashmir a hub of cultural excellence. He introduced administrative reforms, improved irrigation systems, and revitalized agriculture, significantly enhancing the region’s prosperity. Budshah's patronage of artisans and scholars elevated Kashmir’s status as a center of learning and craftsmanship. His emphasis on justice and welfare reflected his deep commitment to his people. This abstract explores the multifaceted achievements of Zain-ul-Abidin and their enduring impact, celebrating his legacy as a beacon of enlightened governance in medieval India.